Effectiveness of Teaching Program on Nurses' Knowledge Concerning the Side Effects of Chemotherapy among Children with Leukemia at Oncology Wards in Baghdad City - Mohammed, asmahan; aburaghif, leila (Iraqi National Journal of Nursing Specialties, 2018)
Objective(s): to assess the effectiveness of educational program on nurses' knowledge concerning the sideeffects of chemotherapy among children with leukemia.Methodology: A descriptive analytic (quasi – experimental) design study was carried out at Baghdad City from2nd of October to 27th of June 2015. Non-probability sample of (35) male and female nurses was selected fromthe Oncology Wards in Children Welfare, Child's Central and Baghdad Teaching Hospital. The studyinstruments consisted of two major parts to meet the purposes of study. The first part is related to nurses'demographic characteristics and the second part (four domains) is related to nurses' knowledge concerning theside effects of chemotherapy. The researcher examined the nurses knowledge for each hospital alone byintroducing the pre-test then, the teaching program of four lectures was given. Every day, a one – hour lecturewas given. Afterward, the post-test. The data were analyzed by using two statistical approaches: Descriptive andInferential statistics.Results: The study revealed that the general knowledge of nurses regarding side effects of chemotherapy was45.7% (Good) for the post-test as opposed to the pre-test which was 51.4% ( acceptable).Recommendation: The study recommended that nurses should be encouraged to attend specific meetings, programs,workshops and seminars in concern of leukemia treatment and side effect of chemotherapy to be acquainted with the mostrecent, advances and skills in the field.